2010
DOI: 10.1021/ol100342m
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Streptomyces platensis MA7339 for Overproduction of Platencin and Congeners

Abstract: Platensimycin (1) and platencin (2) are novel antibiotic leads against multi-drug resistant pathogens. The production of 2 in Streptomyces platensis MA7339 is under the control of ptnR1, a GntR-like transcriptional regulator. Inactivating ptnR1 afforded S. platensis MA7339 mutant strain SB12600 that overproduces 2 at titer ~100-fold greater than that from the wild-type strain and accumulates platencin A 1 (3) and eight new congeners platencin A 2 -A 9 (4-11). The isolation, structural elucidation, and antibact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
106
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(111 citation statements)
references
References 20 publications
5
106
0
Order By: Relevance
“…Finally, we demonstrated the production of PTN by overexpressing the cloned ptn cluster in selected heterologous Streptomyces hosts. We have previously shown that ptmR1 and ptnR1 are transcriptional regulators, and upon inactivation of ptmR1 in MA7327 (25) or ptnR1 in MA7339 (28), respectively, we have yielded mutant strains that significantly overproduce PTN, PTM, or both. We isolated a plasmid pBS12615 that harbors the entire ptn cluster from MA7339, inactivated ptnR1 within the ptn cluster to yield the expression plasmid pBS12619, and introduced pBS12619 into a PTN-nonproducing heterologous host Streptomyces lividans K4-114 (29) to afford the recombinant strain SB12606 (SI Appendix).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Finally, we demonstrated the production of PTN by overexpressing the cloned ptn cluster in selected heterologous Streptomyces hosts. We have previously shown that ptmR1 and ptnR1 are transcriptional regulators, and upon inactivation of ptmR1 in MA7327 (25) or ptnR1 in MA7339 (28), respectively, we have yielded mutant strains that significantly overproduce PTN, PTM, or both. We isolated a plasmid pBS12615 that harbors the entire ptn cluster from MA7339, inactivated ptnR1 within the ptn cluster to yield the expression plasmid pBS12619, and introduced pBS12619 into a PTN-nonproducing heterologous host Streptomyces lividans K4-114 (29) to afford the recombinant strain SB12606 (SI Appendix).…”
Section: Resultsmentioning
confidence: 94%
“…Conversion of the PTN-producing S. platensis MA7339 strain into the PTM and PTN dualproducing S. platensis SB12604 was accomplished by introduction of the PTM cassette from S. platensis MA7327 into S. platensis MA7339. Fermentation of S. platensis wild-type and recombinant strains for PTM and PTN production as well as the production and isolation of PTM and PTN biosynthetic intermediates was performed as described previously, and their structures were confirmed by HPLC analysis with authentic standards as well as mass spectrometry and 1 H and 13 C NMR analyses (25,28). Materials, methods, and detailed experimental procedures are provided in SI Appendix.…”
Section: Methodsmentioning
confidence: 99%
“…Shen's group at the University of Wisconsin used PCR to identify and clone the specific locus of the biosynthetic genes responsible for the production of these compounds, including ptmR1. 37,38 This gene is a negative regulator of transcription. A fragment of the 3-amino-5-hydroxybenzoic (AHBA) synthase gene, which was believed to have a role in the biosynthesis of the benzoic acid moiety of platensimycin, was amplified using this PCR-based approach.…”
Section: Genetic Engineering Of S Platensis Strains For Titer Improvmentioning
confidence: 99%
“…38 Inactivation of the gene ptnR1, a homolog of ptmR1, resulted in about a 100-fold increase in the production of platencin. 37 The new strain, S. platensis SB12600, produced 255 mg l À1 of platencin.…”
Section: Genetic Engineering Of S Platensis Strains For Titer Improvmentioning
confidence: 99%
“…It is just over four years since a group at Merck reported the identification of a novel class of antibiotics called platensimycin [1] or platencin, [2] which are FabF/H inhibitors and therefore inhibit the synthesis of lipids used by bacteria to make cell membranes. In only four years since the seminal report by the Merck group, over 20 groups worldwide have reported the total [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] or enzymatic syntheses [20,21] of platensimycin/platencin or analogues [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] thereof, and about 12 papers [22,23,[28][29][30][31][32][33][34][36]…”
mentioning
confidence: 99%